A viral infection reshapes Arabidopsis water management via root hydraulics, 1 aquaporin downregulation and osmotic adjustment - Manacorda, Carlos Augusto; Cáceres, Pablo D.; Sutka, Moira; Amodeo, Gabriela; Asurmendi, Sebastian; Baroli, Irene (BioRxiv, 2026)
The effect of plant viruses on root water relations and on how roots and shoots coordinate under infection remains poorly understood. Using a hydroponic Arabidopsis thaliana–Turnip mosaic virus (TuMV) pathosystem, we integrated biometric, anatomical, hydraulic, and gas-exchange measurements to dissect how viral infection reshapes root–shoot water relations. TuMV impaired root development, as reflected by an early plateau of primary root elongation. At the functional level, infected plants exhibited a decrease in root hydraulic conductance per unit root mass, concomitant with transcriptional downregulation of root aquaporin genes. Despite this, the relative contribution of aquaporin-mediated water transport, assessed via sodium azide inhibition, remained unchanged, indicating that the virus downregulates total hydraulic capacity without altering the apoplastic–symplastic partitioning of water flow. Gas-exchange analysis revealed a virus-induced decoupling between stomatal conductance and net CO₂ assimilation, resulting in a non-adaptive increase in intrinsic water-use efficiency. This loss of photosynthetic plasticity, combined with shoot-localized osmotic adjustment (more negative leaf osmotic potential and higher relative water content), points to a constrained, suboptimal physiological state. Multivariate analysis confirmed that variation in physiological traits largely drives phenotypic divergence between treatments. Together, these coordinated alterations, reduced root hydraulics, rigid gas-exchange relationships and passive hydraulic matching to a stunted shoot, depict plants locked into a low-performance equilibrium, poorly equipped to compete for water and carbon. This work reveals a systemic hydraulic–photosynthetic reconfiguration that could account for compromises in plant resilience and resource competitiveness.